Language external and language internal factors in the acquisition of gender: the case of Albanian-Greek and English-Greek bilingual children. Issue 8 (13th September 2020) - Kaltsa, Maria; Prentza, Alexandra; Papadopoulou, Despina; Tsimpli, Ianthi Maria
ABSTRACT: The aim of this experimental study is to examine the development of gender assignment and gender agreement in bilingual Albanian-Greek and English-Greek children as well as the exploitation of gender cues on the noun ending in real and pseudo-nouns. Four gender tasks were designed, two targeting gender assignment (determiner + noun production) and two gender agreement (predicate adjective production). Performance is investigated in relation to the role of (positive) L1 transfer (Albanian vs. English), the role of the bilingual's vocabulary knowledge in Greek as well the role of input factors including the monolingual/bilingual school contexts and the role of parental education as a proxy for socioeconomic status (SES). The results show a strong interaction between the bilinguals' performance and their Greek vocabulary development and a negative link between gender accuracy and use of the other language.